1987
DOI: 10.1007/bf00993243
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the 3?-phosphoadenosine-5?-phosphosulfate (PAPS) synthesizing systems of brain and liver

Abstract: Chromatography of brain and liver 100,000 g supernatants over HPLC molecular sieve columns revealed striking differences in the molecular weight distribution of ATP-sulfurylase and APS-kinase of the two tissues, pointing to different enzymic species for both enzymes in brain and liver. This was further substantiated by kinetic characterization of the two enzymes of both tissues. APS-kinase of liver is allosterically activated by ATP, while the brain enzyme is not. ATP-sulfurylase of brain is activated at high,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Although APS kinase has been described in yeast extracts [5] and a variety of other organisms [6][7][8][9][10][11], a thorough kinetic investigation has been carried out only for the fungus, P. chrvysogenum [2,8]. Therefore in order to gain a thorough understanding of the sulphate-activating pathway in mammalian tissues, and to find reasons for the dual defect exhibited by the brachymorphic mouse [12,13], studies of the individual kinase hibited competitive inhibition with APS and non-competitive inhibition with ATP.…”
Section: Introductionmentioning
confidence: 99%
“…Although APS kinase has been described in yeast extracts [5] and a variety of other organisms [6][7][8][9][10][11], a thorough kinetic investigation has been carried out only for the fungus, P. chrvysogenum [2,8]. Therefore in order to gain a thorough understanding of the sulphate-activating pathway in mammalian tissues, and to find reasons for the dual defect exhibited by the brachymorphic mouse [12,13], studies of the individual kinase hibited competitive inhibition with APS and non-competitive inhibition with ATP.…”
Section: Introductionmentioning
confidence: 99%
“…Chase and O'Brien (1970) have identified the formation of 3' -phosphoadenosine-5' -phosphosulfate (PAPS) as a site of action of phenylalanine. It was subsequently shown (Hommes 1985) that it is indeed the PAPS-forming system that is inhibited by phenylalanine, and more specifically the A TP-sulfurylase rather than the adenosine-5' -phosphosulfate(APS)-kinase, the second enzyme of sulfate activation (Matsuo et al 1987a). Those enzymes of liver are not affected by phenylalanine as would be expected since PKU patients show central nervous system pathology, not liver pathology.…”
Section: Effect Of Phenylalanine On Brain Maturation: Implications Fomentioning
confidence: 99%
“…a Studies on the brain enzymes were carried out on the enzyme from fetal calf brain, those on the liver enzymes from rat liver (after Burnell and Roy 1978, Matsuo et al 1987a). bNA: not applicable.…”
Section: Effect Of Phenylalanine On Brain Maturation: Implications Fomentioning
confidence: 99%
“…Suguhara and Schwartz [2,3] ob served a genetically determined defect in the PAPS-forming system in cartilage tissue and liver, but not in the brain, of the brachymorphic mouse. Earlier investigations have shown that the brain PAPS-forming system can be inhibited by phenylalanine, but not that system from liver [4,5], while kinetic dif ferences have been demonstrated between ATP-sulfurylase and APS-kinase of brain and liver, respectively [6]. Inhibition of PAPS synthesis by phenylalanine in the growing rat brain has been shown by Chase and O'Brien [7].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of PAPS synthesis by phenylalanine in the growing rat brain has been shown by Chase and O'Brien [7]. This inhibition has been localized at ATP-sulfurylase [6]. The highest activity of the phenylalanine-sensitive ATP-sulfurylase has been found in those areas of the brain most affected by excess phenylala nine during the period of myelination [8].…”
Section: Introductionmentioning
confidence: 99%